Pendampingan Teknik Pembacaan Tafsir Nusantara pada Kelompok Muda PCINU Jerman - Assa'idi, Sa'dullah; Ruswan, Ruswan; Laila, Azzah Nor; Andriyani, Santi; Almurtadlo, Muhammad Bahruddin (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The young generation of NU Indonesian citizens in Germany is still minimal in terms of skills in reading turat texts of interpretation books, less skilled in preaching. At the socio-cultural level, partners also experience problems in dealing with contemporary problems. So this service program aims to empower NU's younger generation partners, have the capacity of moderate speakers, be able to read interpretations of the archipelago, and analyze contemporary issues. This service method uses the ABCD (Asset Based Community Development) approach. With five stages of steps namely Discovery, Design, Dream, Define, Destiny, and Reflection. The result of this dedication is an increase in partner empowerment reaching 80% in mastering the technique of reading interpretive texts, and compiling fatwas on contemporary issues. At the level of partner satisfaction, 85% of the participants stated that they strongly agreed with the implementation of the activities, presenters, and 80% strongly agreed that the content of the material was according to the needs of partners. The implication of this service program is that partners are more confident, have digital da'wah space to voice moderation and provide wise fatwa solutions to the dynamics of problems faced by Indonesian citizens in Germany.